Ma Orthologous Genes in Prunus spp. Shed Light on a Noteworthy NBS-LRR Cluster Conferring Differential Resistance to Root-Knot Nematodes - Van Ghelder, Cyril; Esmenjaud, Daniel; Callot, Caroline; Dubois, Emeric; Mazier, Marianne; Duval, Henri (Frontiers in Plant Science, 2018)
Root-knot nematodes (RKNs) are considerable polyphagous pests that severely challenge plants worldwide and especially perennials. The specific genetic resistance of plants mainly relies on the NBS-LRR genes that are pivotal factors for pathogens control. In Prunus spp., the Ma plum and RMja almond genes possess different spectra for resistance to RKNs. While previous works based on the Ma gene allowed to clone it and to decipher its peculiar TIR-NBS-LRR (TNL) structure, we only knew that the RMja gene mapped on the same chromosome as Ma. We carried out a high-resolution mapping using an almond segregating F2 progeny of 1448 seedlings from resistant (R) and susceptible (S) parental accessions, to locate precisely RMja on the peach genome, the reference sequence for Prunus species. We showed that the RMja gene maps in the Ma resistance cluster and that the Ma orthologue is the best candidate for RMja. This co-localization is a crucial step that opens the way to unravel the molecular determinants involved in the resistance to RKNs. Then we sequenced both almond parental NGS genomes and aligned them onto the RKN susceptible reference peach genome. We produced a BAC library of the R parental accession and, from two overlapping BAC clones, we obtained a 336-kb sequence encompassing the RMja candidate region. Thus, we could benefit from three Ma orthologous regions to investigate their sequence polymorphism, respectively, within plum (complete R spectrum), almond (incomplete R spectrum) and peach (null R spectrum). We showed that the Ma TNL cluster has evolved orthologues with a unique conserved structure comprised of five repeated post-LRR (PL) domains, which contain most polymorphism. In addition to support the Ma and RMja orthologous relationship, our results suggest that the polymorphism contained in the PL sequences might underlie differential resistance interactions with RKNs and an original immune mechanism in woody perennials. Besides, our study illustrates how PL exon duplications and losses shape TNL structure and give rise to atypical PL domain repeats of yet unknown role.